Prevalence of Muscle Dysmorphia and its Relationship with Eating Disorders in Adolescent Males - Lugo-Salazar, Kenia Jocelyne (2026)
Introduction: Muscle Dysmorphic (MD) is characterizedby an obsession with exercise aimed at increasing muscle mass, which may involve restrictive diets and the use of supplements (Torres-Mota et al., 2021). It has been defined as a body image disorder, with predisposing, triggering, and maintaining factors identified, such as personality traits, body dissatisfaction, and behaviors aimed at increasingmuscle mass, respectively (Rabito-Alcón y Rodríguez-Molina, 2016). Objective: Analyze the prevalence of Muscle Dysmorphia in adolescent males and its relationship with Eating Disorders. Methodology: A cross-sectional and correlational study was conducted with 460 adolescents, with an average age of 16 years (SD = 1). Two validated instruments for the Mexican population were used: the Eating Attitudes Test-26 and the Muscle Appearance Satisfaction Scale. Results: A significant relationship was found (r = .354**) between Muscle Dysmorphic Disorder and Eating Disorders (ED). It was identified that 52% of adolescents have no or low risk, 41% have a moderate risk, and 7% have a high risk. The level of MD predicts the risk of ED in men by 12.5%. Conclusion: Most adolescents exhibit low to moderate risk levels for MDD, while seven out of every hundred adolescents present a high risk. Additionally, a direct, positive, and significant correlation was found between MDD and ED, indicating that as MDD scores increase, ED scores also rise, and conversely.